Association of child labor with risk and protective factors for Chronic Noncommunicable Diseases in Brazilian schoolchildren: National School Health Survey 2015 - Alan Cristian Marinho Ferreira; Alanna Gomes da Silva; Crizian Saar Gomes; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the sociodemographic profile of adolescents working in Brazil and the association of child labor with risk and protection factors for Chronic Noncommunicable Diseases. Methods: Cross-sectional study with data from sample 2 of the 2015 National School Health Survey (PeNSE). The variables gender, age, ethnicity/skin color, administrative dependence on school and maternal education, eating habits, physical activity and drug use were analyzed by prevalence and respective 95% confidence intervals (95%CI) and calculation of crude and adjusted Odds Ratio. Results: A total of 10,926 students participated in the survey, of which 16.9% (95%CI 15.1-18.9) were currently working/employed. Child labor was higher among male adolescents (ORa: 1.82; 95%CI 1.55-2.15); aged between 16 and 17 years (ORa: 2.96; 95%CI 2.37-3.69); enrolled in public schools (ORa: 1.69; 95%CI 1.14-2.52); whose mothers had incomplete high school (ORa: 1.54; 95%CI 1.11-2.13); living in the South region of the country (ORa: 2.17; 95%CI 1.60-2.94). Adolescents who worked were more likely to smoke (ORa: 1.94; 95%CI 1.52-2.48); use alcohol (ORa: 2.01; 95%CI 1.71-2.36) and drugs (ORa: 1.76; 95%CI 1.35-2.31); perform physical activity (ORa: 1.24; 95%CI 1.07-1.44); consume sweets (ORa: 1.30; 95%CI 1.13-1.49), fried snacks (ORa: 1.41; 95%CI 1.15-1.74), and soft drinks (ORa: 1.23; 95%CI 1.06-1.44); however, they were less likely to present sedentary behavior (ORa: 0.68; 95%CI 0.59-0.79). Conclusion: Child labor in Brazil is related to sociodemographic differences. Those who worked were more likely to show risk behaviors for NCDs, but they were more physically active.